Negative electrode material for lithium ion button battery and preparation method of negative electrode material

Through the composite treatment of chitosan and phytic acid modified nanosilicon powder and Mn-Ce modified biochar material, the problem of limited performance of the negative electrode material of lithium-ion batteries is solved, and the battery capacity retention rate and cycle stability are improved.

CN119601633AActive Publication Date: 2025-03-11SHANDONG HUATAI NEW ENERGY BATTERY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411789744.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The performance of the negative electrode material of lithium-ion batteries is limited, resulting in battery capacity attenuation and deterioration of cycling performance, limiting the practical application of silicon-based materials in lithium-ion batteries.

Method used

Chitosan and phytic acid modified nanosilicon powder are combined with Mn-Ce modified biochar material, and the negative electrode material with excellent electrochemical properties is formed by ball milling and high-temperature calcination.

Benefits of technology

This method effectively alleviates the volume expansion problem of silicon material during charging and discharging, increases ion migration channels and electron conduction paths, and improves the capacity retention rate and cycling stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601633A_ABST
    Figure CN119601633A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode material for a lithium ion button battery and a preparation method of the negative electrode material, and belongs to the technical field of battery materials. The lithium battery negative electrode material prepared by compounding the Mn-Ce modified biochar material and the chitosan-phytic acid modified nano silicon powder according to a specific ratio can effectively relieve the volume expansion problem of the silicon material in the charge-discharge process, and can increase more ion migration channels and enhance electron conduction paths at the same time; the composite material has excellent electrochemical performance, improves the capacity retention ratio and cycling stability of the lithium ion battery, and has a good market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a negative electrode material for a lithium-ion button battery and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, applications such as portable electronic devices and electric vehicles have increasing requirements for energy storage devices. Lithium-ion batteries (LIBs) have become the preferred energy storage devices in these fields due to their outstanding advantages such as high voltage, high energy density, good cycle performance and low self-discharge. However, the performance of lithium-ion batteries depends largely on the selection and performance of their negative electrode materials. Traditional lithium-ion battery negative electrode materials mainly include carbon materials such as graphite, hard carbon and soft carbon. Among them, graphite, as a traditional negative electrode material, has relatively stable electrochemical properties and low cost, but its theoretical specific capacity is only 372mAh / g, which limits the further improvement of the energy density of lithium-ion batteries. Silicon-based materials (such as SiO x , Sn, SnO2, etc.) have attracted much attention due to their relatively high specific capacity characteristics. However, silicon-based materials have problems such as poor conductivity and large volume changes (up to more than 200%) during the process of embedding / de-embedding lithium ions. This characteristic causes battery capacity decay and cycle performance deterioration in two aspects when used as negative electrode materials. On the one hand, the destruction of the material structure and mechanical pulverization cause the separation of the negative electrode material and the current collector, which physically reduces the battery capacity and cycle performance; on the other hand, the expansion and contraction of the volume causes the continuous rupture and reconstruction of the SEI film, which continuously consumes active materials, causing adverse effects such as battery capacity decay and cycle performance deterioration. These problems seriously limit the practical application of silicon-based materials in lithium-ion batteries.

[0003] In order to solve the above problems, researchers have conducted a lot of research and exploration. The performance of negative electrode materials can usually be improved through structural design. For example, by constructing a three-dimensional structure, introducing a porous skeleton or using a composite material, the lithium ion storage capacity, lithium ion transfer rate and cycle stability of the negative electrode material can be effectively improved; in addition, surface doping or coating modification of the negative electrode material can also improve its electrochemical properties and conductivity. The most common modification is the modification of carbon-silicon composite materials. However, the existing preparation methods of silicon-carbon composite materials still have certain shortcomings, such as limited selection of carbon sources, high cost and poor effect, and no obvious improvement in cycle performance. Summary of the invention

[0004] The present invention aims to provide a high-performance negative electrode material for lithium-ion button batteries to meet the needs of portable electronic devices and electric vehicles for high-performance energy storage devices.

[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is: A method for preparing a negative electrode material for a lithium ion button battery comprises the following steps: (1) Dissolve chitosan in 5 wt% citric acid solution, heat in a 55°C water bath and stir for 30 min to obtain solution A; (2) Adding nano silicon powder into 10 wt% phytic acid solution according to the material-liquid ratio, stirring evenly to obtain suspension B; (3) After solution A and suspension B are mixed according to the mass ratio, they are first subjected to ultrasonic treatment for 30 min and then magnetically stirred in a water bath at 60°C for 30 min. After the reaction is completed, the mixture is filtered and washed with deionized water until neutral, and then dried in a vacuum drying oven to obtain modified nano-silicon powder; (4) Wash the walnut shells, dry and crush them, and pass them through a 100-mesh sieve to obtain walnut shell powder. Then take 5g of walnut shell powder and disperse it in 200ml of deionized water. Add 0.02mol of MnCl2 and 0.04mol of Ce(NO3)3 respectively, stir evenly and disperse them by ultrasonic for 2h. After solid-liquid separation, the solid product is placed in an oven for drying, and then transferred to a tubular furnace, and nitrogen protection is introduced. It is calcined at high temperature for 2h. After cooling to room temperature, it is washed with deionized water for 3-5 times, and then dried and crushed. After passing through a 100-mesh sieve, the Mn-Ce modified biochar material is obtained; (5) The modified nano-silicon powder and the Mn-Ce modified biochar material are mixed in a mass ratio and placed in a ball mill at a ball-to-liquid ratio of 5:1. Anhydrous ethanol is then added as a ball milling medium at a material-liquid ratio of 1:4. The speed is set to 400 rpm and the ball milling treatment is performed for 10-12 h. The mixture is transferred into a tubular furnace and argon is introduced as a protective gas. The mixture is calcined at a high temperature, naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

[0006] Preferably, in step (1), the material-liquid ratio of chitosan to citric acid solution is 1 g:50 ml.

[0007] Preferably, in step (2), the material-liquid ratio of nano silicon powder to phytic acid solution is 1 g:20 ml.

[0008] Preferably, in step (3), the mass ratio of solution A to suspension B is 1:2.

[0009] Preferably, the specific calcination method in step (4) is: heating to 600° C. at a rate of 10° C. / min and then keeping the temperature for 2 h.

[0010] Preferably, in step (5), the mass ratio of the modified nano-silicon powder to the Mn-Ce modified biochar material is 1:2-5.

[0011] Preferably, the specific method of high temperature calcination in step (5) is: heating to 800° C. at a rate of 5° C. / min and then keeping the temperature for 2 h.

[0012] The present invention also provides a negative electrode material for a lithium ion button battery prepared by the above-mentioned method for preparing a negative electrode material for a lithium ion button battery, which can effectively alleviate the volume expansion problem of the silicon material during the charge and discharge process, and can also increase more ion migration channels and enhance the electron conduction path. It has excellent electrochemical properties, improves the capacity retention rate and cycle stability of the lithium ion battery, and has good market application prospects.

[0013] The negative electrode material for lithium ion button battery prepared by the above method is used as follows: the negative electrode material prepared by the present invention is fully ground and then ground and stirred with conductive black and binder in a mass ratio of 8:1:1 to form a uniformly dispersed slurry, and then coated on a copper foil with an I-shaped scraper, with a slurry thickness of 75 μm. Dry in a vacuum drying oven at 60°C for 12 h, take out and cut into discs with a diameter of 10 mm on a slicer and press at a pressure of 6 MPa to obtain a negative electrode sheet.

[0014] The nano silicon powder used in the present invention is a commercially available product with a particle size of 100 nm. The other raw materials and reagents used can be purchased from the market unless otherwise specified.

[0015] The beneficial effects of the present invention are: (1) Chitosan and phytic acid are both natural biomolecular active substances, containing functional groups such as amino, hydroxyl and phosphoric acid. These functional groups are simultaneously adsorbed on the surface of nanosilicon through chemical bonds, which enhances the interaction between nanosilicon materials and biological small molecules, thereby being more conducive to reducing the surface activity of silicon and promoting the formation of a more complete and stable SEI film, which can better resist the volume expansion of silicon materials and reduce the occurrence of side reactions between active substances and electrolytes.

[0016] (2) Walnut shell biochar itself is a renewable resource, and its preparation process helps reduce environmental pollution and greenhouse gas emissions. Biochar prepared from walnut shells has a large specific surface area and rich porous structure. The use of Mn-Ce modified biochar material further optimizes its pore structure and surface chemical properties by introducing Mn and Ce elements, improving the adsorption and desorption capacity of lithium ions, thereby increasing the energy density of the battery. At the same time, Mn-Ce modified biochar also enhances the structural stability of the biochar material, reduces structural damage during the charging and discharging process, and thus prolongs the cycle life of the battery.

[0017] (3) The chitosan-phytic acid modified nano-silicon powder is coated with chitosan and phytic acid, which enhances the stability and dispersibility of nano-silicon, while also improving its conductivity and cycle stability. When used in combination with Mn-Ce modified biochar, the two work synergistically to further enhance the conductivity and cycle stability of the negative electrode material, improve the specific capacity, and have good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The surface morphology of the negative electrode material prepared in Example 3 of the present invention at different resolutions, wherein a is a low-resolution SEM image and b is a high-resolution SEM image; Figure 2 This is a graph showing the electrochemical cycle performance test results of negative electrode materials A1, A2, A3 and A4 for lithium-ion button batteries prepared by mixing raw materials in different proportions of the present invention. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.

[0020] Example 1 A method for preparing a negative electrode material for a lithium ion button battery comprises the following steps: (1) Dissolve 2 g of chitosan in 100 ml of 5 wt% citric acid solution, heat in a 55 °C water bath and stir for 30 min to obtain solution A; (2) Add 5 g of nano-silicon powder to 100 ml of 10 wt% phytic acid solution and stir evenly to obtain suspension B; (3) Solution A and suspension B were mixed in a mass ratio of 1:2, and then ultrasonically treated for 30 min and then magnetically stirred in a water bath at 60°C for 30 min. After the reaction was completed, the mixture was filtered and washed with deionized water until neutral, and then dried in a vacuum drying oven to obtain modified nano-silicon powder. (4) Wash the walnut shells, dry and crush them, and pass them through a 100-mesh sieve to obtain walnut shell powder. Then take 5g of walnut shell powder and disperse it in 200ml of deionized water. Add 0.02mol of MnCl2 and 0.04mol of Ce(NO3)3 respectively, stir evenly and disperse them by ultrasonic for 2h. After solid-liquid separation, the solid product is placed in an oven for drying, and then transferred to a tubular furnace, nitrogen protection is introduced, and the temperature is increased to 600℃ at a rate of 10℃ / min and kept warm for 2h. After cooling to room temperature, wash with deionized water for 3-5 times, and then dry and crush them. After passing through a 100-mesh sieve, the Mn-Ce modified biochar material is obtained; (5) The modified nano-silicon powder and the Mn-Ce modified biochar material were mixed in a mass ratio of 1:2 and placed in a ball mill at a ball-to-liquid ratio of 5:1. Anhydrous ethanol was then added as a ball milling medium at a material-liquid ratio of 1:4. The speed was set to 400 rpm and the ball milling treatment was performed for 10 h. The mixture was transferred into a tubular furnace and argon was introduced as a protective gas. The temperature was raised to 800 °C at a rate of 5 °C / min and then kept at this temperature for 2 h. The mixture was naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

[0021] Example 2 A method for preparing a negative electrode material for a lithium ion button battery comprises the following steps: (1) Dissolve 2 g of chitosan in 100 ml of 5 wt% citric acid solution, heat in a 55 °C water bath and stir for 30 min to obtain solution A; (2) Add 5 g of nano-silicon powder to 100 ml of 10 wt% phytic acid solution and stir evenly to obtain suspension B; (3) Solution A and suspension B were mixed in a mass ratio of 1:2, and then ultrasonically treated for 30 min and then magnetically stirred in a water bath at 60°C for 30 min. After the reaction was completed, the mixture was filtered and washed with deionized water until neutral, and then dried in a vacuum drying oven to obtain modified nano-silicon powder. (4) Wash the walnut shells, dry and crush them, and pass them through a 100-mesh sieve to obtain walnut shell powder. Then take 5g of walnut shell powder and disperse it in 200ml of deionized water. Add 0.02mol of MnCl2 and 0.04mol of Ce(NO3)3 respectively, stir evenly and disperse them by ultrasonic for 2h. After solid-liquid separation, the solid product is placed in an oven for drying, and then transferred to a tubular furnace, nitrogen protection is introduced, and the temperature is increased to 600℃ at a rate of 10℃ / min and kept warm for 2h. After cooling to room temperature, wash with deionized water for 3-5 times, and then dry and crush them. After passing through a 100-mesh sieve, the Mn-Ce modified biochar material is obtained; (5) The modified nano-silicon powder and the Mn-Ce modified biochar material were mixed in a mass ratio of 1:3 and placed in a ball mill at a ball-to-liquid ratio of 5:1. Anhydrous ethanol was then added as a ball milling medium at a material-liquid ratio of 1:4. The speed was set to 400 rpm and the ball milling treatment was performed for 11 h. The mixture was transferred into a tubular furnace and argon was introduced as a protective gas. The temperature was raised to 800 °C at a rate of 5 °C / min and then kept at this temperature for 2 h. The mixture was naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

[0022] Example 3 A method for preparing a negative electrode material for a lithium ion button battery comprises the following steps: (1) Dissolve 2 g of chitosan in 100 ml of 5 wt% citric acid solution, heat in a 55 °C water bath and stir for 30 min to obtain solution A; (2) Add 5 g of nano-silicon powder to 100 ml of 10 wt% phytic acid solution and stir evenly to obtain suspension B; (3) Solution A and suspension B were mixed in a mass ratio of 1:2, and then ultrasonically treated for 30 min and then magnetically stirred in a water bath at 60°C for 30 min. After the reaction was completed, the mixture was filtered and washed with deionized water until neutral, and then dried in a vacuum drying oven to obtain modified nano-silicon powder. (4) Wash the walnut shells, dry and crush them, and pass them through a 100-mesh sieve to obtain walnut shell powder. Then take 5g of walnut shell powder and disperse it in 200ml of deionized water. Add 0.02mol of MnCl2 and 0.04mol of Ce(NO3)3 respectively, stir evenly and disperse them by ultrasonic for 2h. After solid-liquid separation, the solid product is placed in an oven for drying, and then transferred to a tubular furnace, nitrogen protection is introduced, and the temperature is increased to 600℃ at a rate of 10℃ / min and kept warm for 2h. After cooling to room temperature, wash with deionized water for 3-5 times, and then dry and crush them. After passing through a 100-mesh sieve, the Mn-Ce modified biochar material is obtained; (5) The modified nano-silicon powder and the Mn-Ce modified biochar material were mixed in a mass ratio of 1:5, and placed in a ball mill at a ball-to-liquid ratio of 5:1. Then, anhydrous ethanol was added as a ball milling medium at a material-liquid ratio of 1:4. The speed was set to 400 rpm and the ball milling treatment was performed for 12 h. The mixture was transferred into a tubular furnace, and argon was introduced as a protective gas. The temperature was increased to 800 °C at a rate of 5 °C / min and then kept at this temperature for 2 h. The mixture was naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

[0023] Comparative Example 1 A method for preparing a negative electrode material for a lithium ion button battery comprises the following steps: (1) Wash the walnut shells, dry and crush them, and pass them through a 100-mesh sieve to obtain walnut shell powder. Then, transfer the walnut shell powder into a tubular furnace, introduce nitrogen protection, heat it to 600°C at a rate of 10°C / min, keep it warm for 2 hours, cool it to room temperature, crush it, and pass it through a 100-mesh sieve to obtain biochar material; (2) Nano-silicon powder and biochar were mixed in a mass ratio of 1:5 and placed in a ball mill at a ball-to-liquid ratio of 5:1. Anhydrous ethanol was then added as a ball milling medium at a material-liquid ratio of 1:4. The speed was set to 400 rpm and the ball milling treatment was performed for 12 h. The mixture was transferred into a tubular furnace and argon was introduced as a protective gas. The temperature was raised to 800 °C at a rate of 5 °C / min and then kept at this temperature for 2 h. The mixture was naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

[0024] Comparative Example 2 A method for preparing a negative electrode material for a lithium ion button battery comprises the following steps: (1) Dissolve 2 g of chitosan in 100 ml of 5 wt% citric acid solution, heat in a 55 °C water bath and stir for 30 min to obtain solution A; (2) Add 5 g of nano-silicon powder to 100 ml of 10 wt% phytic acid solution and stir evenly to obtain suspension B; (3) Solution A and suspension B were mixed in a mass ratio of 1:2, and then ultrasonically treated for 30 min and then magnetically stirred in a water bath at 60°C for 30 min. After the reaction was completed, the mixture was filtered and washed with deionized water until neutral, and then dried in a vacuum drying oven to obtain modified nano-silicon powder. (4) Wash the walnut shells, dry and crush them, pass them through a 100-mesh sieve to obtain walnut shell powder, then transfer them into a tubular furnace, introduce nitrogen protection, heat them to 600°C at a rate of 10°C / min, keep them warm for 2 hours, cool them to room temperature, crush them, and pass them through a 100-mesh sieve to obtain biochar material; (5) The modified nano-silicon powder and biochar material were mixed in a mass ratio of 1:5, and placed in a ball mill at a ball-to-liquid ratio of 5:1. Anhydrous ethanol was then added as a ball milling medium at a material-liquid ratio of 1:4. The speed was set to 400 rpm and the ball milling treatment was performed for 12 h. The mixture was transferred to a tubular furnace, and argon was introduced as a protective gas. The mixture was calcined at high temperature, naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

[0025] This comparative example is basically the same as Example 3, except that the biochar used is unmodified biochar material.

[0026] Comparative Example 3 A method for preparing a negative electrode material for a lithium ion button battery comprises the following steps: (1) Wash the walnut shell, dry it, and grind it to obtain walnut shell powder after passing through a 100-mesh sieve. Then, take 5 g of walnut shell powder and disperse it in 200 ml of deionized water. Add 0.02 mol of MnCl2 and 0.04 mol of Ce(NO3)3 respectively, stir evenly and disperse it by ultrasonic for 2 h. After solid-liquid separation, the solid product is placed in an oven for drying, and then transferred to a tubular furnace, and nitrogen is introduced for protection. The temperature is increased to 600 °C at a rate of 10 °C / min and then kept at this temperature for 2 h. After cooling to room temperature, it is washed with deionized water for 3-5 times, then dried and ground, and passed through a 100-mesh sieve to obtain Mn-Ce modified biochar material; (2) Nano-silicon powder and Mn-Ce modified biochar material were mixed in a mass ratio of 1:5, and placed in a ball mill at a ball-to-liquid ratio of 5:1. Anhydrous ethanol was then added as a ball milling medium at a material-liquid ratio of 1:4. The speed was set to 400 rpm and the ball milling treatment was performed for 12 h. The mixture was transferred into a tubular furnace, and argon was introduced as a protective gas. The mixture was calcined at high temperature, naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

[0027] This comparative example is basically the same as Example 3, except that the nano silicon powder is not modified.

[0028] Comparative Example 4 A method for preparing a negative electrode material for a lithium ion button battery comprises the following steps: (1) Dissolve 2 g of chitosan in 100 ml of 5 wt% citric acid solution, heat in a 55 °C water bath and stir for 30 min to obtain solution A; (2) Add 5 g of nano-silicon powder to 100 ml of 10 wt% phytic acid solution and stir evenly to obtain suspension B; (3) Solution A and suspension B were mixed in a mass ratio of 1:2, and then ultrasonically treated for 30 min and then magnetically stirred in a water bath at 60°C for 30 min. After the reaction was completed, the mixture was filtered and washed with deionized water until neutral, and then dried in a vacuum drying oven to obtain modified nano-silicon powder. (4) Wash the walnut shells, dry and crush them, and pass them through a 100-mesh sieve to obtain walnut shell powder. Then take 5g of walnut shell powder and disperse it in 200ml of deionized water. Add 0.02mol of MnCl2 to each of them, stir evenly and ultrasonically disperse them for 2h. After solid-liquid separation, the solid product is placed in an oven for drying, and then transferred to a tubular furnace, nitrogen protection is introduced, and the temperature is increased to 600℃ at a rate of 10℃ / min and then kept warm for 2h. After cooling to room temperature, it is washed with deionized water for 3-5 times, and then dried and crushed. After passing through a 100-mesh sieve, the Mn-modified biochar material is obtained; (5) The modified nano-silicon powder and the Mn-modified biochar material were mixed in a mass ratio of 1:5, and placed in a ball mill at a ball-to-liquid ratio of 5:1. Then, anhydrous ethanol was added as a ball milling medium at a material-liquid ratio of 1:4. The speed was set to 400 rpm and the ball milling treatment was performed for 12 h. The mixture was transferred into a tubular furnace, and argon was introduced as a protective gas. The temperature was increased to 800 °C at a rate of 5 °C / min and then kept at this temperature for 2 h. The mixture was naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

[0029] This comparative example is basically the same as Example 3, except that the modified biochar is only modified using MnCl2.

[0030] Comparative Example 5 A method for preparing a negative electrode material for a lithium ion button battery comprises the following steps: (1) Dissolve 2 g of chitosan in 100 ml of 5 wt% citric acid solution, heat in a 55 °C water bath and stir for 30 min to obtain solution A; (2) Add 5 g of nano-silicon powder to 100 ml of 10 wt% phytic acid solution and stir evenly to obtain suspension B; (3) Solution A and suspension B were mixed in a mass ratio of 1:2, and then ultrasonically treated for 30 min and then magnetically stirred in a water bath at 60°C for 30 min. After the reaction was completed, the mixture was filtered and washed with deionized water until neutral, and then dried in a vacuum drying oven to obtain modified nano-silicon powder. (4) Wash the walnut shells, dry and crush them, and pass them through a 100-mesh sieve to obtain walnut shell powder. Then take 5g of walnut shell powder and disperse it in 200ml of deionized water. Add 0.04mol of Ce(NO3)3 to each of them, stir evenly and ultrasonically disperse them for 2h. After solid-liquid separation, the solid product is placed in an oven for drying, and then transferred to a tubular furnace, nitrogen protection is introduced, and the temperature is increased to 600℃ at a rate of 10℃ / min and then kept warm for 2h. After cooling to room temperature, it is washed with deionized water for 3-5 times, and then dried and crushed. After passing through a 100-mesh sieve, Ce-modified biochar material is obtained; (5) The modified nano-silicon powder and the Ce-modified biochar material were mixed in a mass ratio of 1:5, and placed in a ball mill at a ball-to-liquid ratio of 5:1. Then, anhydrous ethanol was added as a ball milling medium at a material-liquid ratio of 1:4. The speed was set to 400 rpm and the ball milling treatment was performed for 12 h. The mixture was transferred into a tubular furnace, and argon was introduced as a protective gas. The temperature was increased to 800 °C at a rate of 5 °C / min and then kept at this temperature for 2 h. The mixture was naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

[0031] This comparative example is basically the same as Example 3, with the only difference being that the modified biochar is only modified using Ce(NO3)3.

[0032] Comparative Example 6 A method for preparing a negative electrode material for a lithium ion button battery comprises the following steps: (1) Dissolve 2 g of chitosan in 100 ml of 5 wt% citric acid solution, heat in a 55 °C water bath and stir for 30 min to obtain solution A; (2) Add 5 g of nano-silicon powder to solution A, treat with ultrasound for 30 min, and then stir in a water bath at 60°C with magnetic stirring for 30 min. After the reaction is completed, filter and wash with deionized water until neutral, and then dry in a vacuum drying oven to obtain modified nano-silicon powder. (3) Wash the walnut shells, dry and crush them, and pass them through a 100-mesh sieve to obtain walnut shell powder. Then take 5g of walnut shell powder and disperse it in 200ml of deionized water. Add 0.02mol of MnCl2 and 0.04mol of Ce(NO3)3 respectively, stir evenly and disperse them by ultrasonic for 2h. After solid-liquid separation, the solid product is placed in an oven for drying, and then transferred to a tubular furnace, nitrogen protection is introduced, and the temperature is increased to 600℃ at a rate of 10℃ / min and kept warm for 2h. After cooling to room temperature, it is washed with deionized water for 3-5 times, and then dried and crushed. After passing through a 100-mesh sieve, Mn-Ce modified biochar material is obtained; (4) The modified nano-silicon powder and the Mn-Ce modified biochar material were mixed in a mass ratio of 1:5, and placed in a ball mill at a ball-to-liquid ratio of 5:1. Then, anhydrous ethanol was added as a ball milling medium at a material-liquid ratio of 1:4. The speed was set to 400 rpm and the ball milling treatment was performed for 12 h. The mixture was transferred into a tubular furnace, and argon was introduced as a protective gas. The temperature was increased to 800 °C at a rate of 5 °C / min and then kept at this temperature for 2 h. The mixture was naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

[0033] This comparative example is basically the same as Example 3, except that the modified nano-silicon powder is only modified with chitosan.

[0034] Comparative Example 7 A method for preparing a negative electrode material for a lithium ion button battery comprises the following steps: (1) Add 5 g of nano-silicon powder to 100 ml of 10 wt% phytic acid solution and stir evenly to obtain suspension B; (2) The suspension B was first subjected to ultrasonic treatment for 30 min and then magnetically stirred in a water bath at 60°C for 30 min. After the reaction was completed, the suspension was filtered and washed with deionized water until neutral, and then dried in a vacuum drying oven to obtain modified nano-silicon powder. (3) Wash the walnut shells, dry and crush them, and pass them through a 100-mesh sieve to obtain walnut shell powder. Then take 5g of walnut shell powder and disperse it in 200ml of deionized water. Add 0.02mol of MnCl2 and 0.04mol of Ce(NO3)3 respectively, stir evenly and disperse them by ultrasonic for 2h. After solid-liquid separation, the solid product is placed in an oven for drying, and then transferred to a tubular furnace, nitrogen protection is introduced, and the temperature is increased to 600℃ at a rate of 10℃ / min and kept warm for 2h. After cooling to room temperature, it is washed with deionized water for 3-5 times, and then dried and crushed. After passing through a 100-mesh sieve, Mn-Ce modified biochar material is obtained; (4) The modified nano-silicon powder and the Mn-Ce modified biochar material were mixed in a mass ratio of 1:5, and placed in a ball mill at a ball-to-liquid ratio of 5:1. Then, anhydrous ethanol was added as a ball milling medium at a material-liquid ratio of 1:4. The speed was set to 400 rpm and the ball milling treatment was performed for 12 h. The mixture was transferred into a tubular furnace, and argon was introduced as a protective gas. The temperature was increased to 800 °C at a rate of 5 °C / min and then kept at this temperature for 2 h. The mixture was naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

[0035] This comparative example is basically the same as Example 3, except that the modified nano silicon powder is only modified with phytic acid.

[0036] Performance Testing The electrochemical performance of the negative electrode materials for lithium-ion button batteries prepared in Examples 1-3 and Comparative Examples 1-7 was tested, and the specific steps were as follows: Preparation of negative electrode sheet: After the negative electrode material prepared by the present invention is fully ground, it is ground with acetylene black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 8:1:1, and then an appropriate amount of NMP (N-methylpyrrolidone) is added, and stirring is continued until it becomes a paste, and then it is coated on a copper foil with an I-shaped scraper, and the slurry thickness is 75 μm. Dry it in a vacuum drying oven at 60°C for 12 h, take it out, cut it into a disc with a diameter of 12 mm on a slicer, and press it at a pressure of 6 MPa to obtain a negative electrode sheet for a lithium battery.

[0037] Battery assembly: Using the above-mentioned electrode sheet as the negative electrode and the metal lithium sheet as the positive electrode, CR-2032 button cells were assembled in an argon atmosphere glove box. The diaphragm model was Celgard 2400, and the electrolyte was 1 mol / L LiPF6 conductive salt and DMC:DEC:EC (wt%) = 1:1:1 solvent; after the assembly was allowed to stand for 12 h, various electrochemical performance tests were carried out.

[0038] The battery charge and discharge test system was used to perform cyclic charge and discharge tests at a set current density, with a voltage range of 0.01~2.00 V. First, 3 cycles were activated with a current density of 50 mA / g, and then a long cycle test was performed with a current density of 100 mA / g. The specific test results are shown in Table 1.

[0039] Table 1 Performance test results From the data in the above table, it can be seen that the first discharge specific capacity of the negative electrode material of the lithium battery prepared in the embodiment of the present invention is 3741mAh / g, the first coulomb efficiency is above 92%, and after 400 cycles, the capacity retention rate is above 87%, which shows that the negative electrode material prepared by the present invention has excellent electrochemical performance, and the modified biochar and nano silicon powder work synergistically to promote the formation of a more complete and stable SEI film, which can better resist the volume expansion of the silicon material, and reduce the occurrence of side reactions between the active substance and the electrolyte, thereby improving the specific capacity and cycle stability of the battery material. However, the negative electrode material prepared by changing any raw material composition in Comparative Examples 1-7 has a decreased battery performance, which is due to the disappearance of the interaction between the modified nano silicon powder and the Mn-Ce modified biochar material.

[0040] The surface morphology of the negative electrode material for lithium ion button battery prepared in Example 3 of the present invention was tested by SEM. The results are as follows: Figure 1As shown in the figure, it can be seen that the material is an irregular block or granular material, and a large number of micro- and nano-sized particulate matter appear on the surface. This is due to the successful loading of modified Mn-Ce metal particles and nano-silicon particles on biochar particles. Mn-Ce modified biochar further optimizes its pore structure and surface chemical properties, improves the adsorption and desorption capacity of lithium ions, and thus increases the energy density of the battery. The nano-silicon powder modified with chitosan-phytic acid is coated with chitosan and phytic acid, which enhances the stability and dispersibility of nano-silicon. The two are uniformly and stably adsorbed together, and at the same time, its conductivity and cycle stability are improved.

[0041] The present invention also studies the negative electrode materials A1, A2 and A3 for lithium ion button batteries prepared by mixing modified nano silicon powder with Mn-Ce modified biochar material in a mass ratio of 1:1, 1:6 and 1:7, respectively. The negative electrode materials A1, A2 and A3 for lithium ion button batteries obtained by Example 3 (denoted as A4) are tested for electrochemical properties by the same test method as above. The cycle performance test results are as follows: Figure 2 shown.

[0042] From the above Figure 2 It can be seen from the contents that by changing the raw material ratio of the present invention, the electrochemical performance of the negative electrode material is significantly deteriorated, and the raw material composition ratio of the present invention is the best ratio.

[0043] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a negative electrode material for a lithium-ion button battery, characterized in that: It includes the following steps: (1) Dissolve chitosan in 5 wt% citric acid solution, heat in a 55°C water bath and stir for 30 min to obtain solution A; (2) Adding nano silicon powder into 10 wt% phytic acid solution according to the material-liquid ratio, stirring evenly to obtain suspension B; (3) After solution A and suspension B are mixed according to the mass ratio, they are first subjected to ultrasonic treatment for 30 minutes and then magnetically stirred in a water bath at 60°C for 30 minutes. After the reaction is completed, the mixture is filtered and washed with deionized water until neutral, and then dried in a vacuum drying oven to obtain modified nano-silicon powder; (4) Wash the walnut shells, dry and crush them, and pass them through a 100-mesh sieve to obtain walnut shell powder. Then take 5g of walnut shell powder and disperse it in 200ml of deionized water. Add 0.02mol of MnCl2 and 0.04mol of Ce(NO3)3 respectively, stir evenly and disperse them by ultrasonic for 2h. After solid-liquid separation, the solid product is placed in an oven for drying, and then transferred to a tubular furnace, and nitrogen protection is introduced. It is calcined at high temperature for 2h. After cooling to room temperature, it is washed with deionized water for 3-5 times, and then dried and crushed. After passing through a 100-mesh sieve, the Mn-Ce modified biochar material is obtained; (5) The modified nano-silicon powder and the Mn-Ce modified biochar material are mixed in a mass ratio and placed in a ball mill at a ball-to-liquid ratio of 5:

1. Anhydrous ethanol is then added as a ball milling medium at a material-liquid ratio of 1:

4. The speed is set to 400 rpm and the ball milling treatment is performed for 10-12 h. The mixture is transferred into a tubular furnace and argon is introduced as a protective gas. The mixture is calcined at a high temperature, naturally cooled and ground to obtain the negative electrode material for lithium-ion button batteries.

2. The method for preparing a negative electrode material for a lithium ion button battery according to claim 1, characterized in that: In the step (1), the material-liquid ratio of chitosan to citric acid solution is 1 g:50 ml.

3. The method for preparing a negative electrode material for a lithium ion button battery according to claim 1, characterized in that: In the step (2), the material-liquid ratio of nano silicon powder to phytic acid solution is 1 g:20 ml.

4. The method for preparing a negative electrode material for a lithium ion button battery according to claim 1, characterized in that: In step (3), the mass ratio of solution A to suspension B is 1:

2.

5. The method for preparing a negative electrode material for a lithium ion button battery according to claim 1, characterized in that: The specific calcination method in step (4) is: heating to 600° C. at a rate of 10° C. / min and then keeping the temperature for 2 h.

6. The method for preparing a negative electrode material for a lithium ion button battery according to claim 1, characterized in that: In the step (5), the mass ratio of the modified nano-silicon powder to the Mn-Ce modified biochar material is 1:2-5.

7. The method for preparing a negative electrode material for a lithium ion button battery according to claim 1, characterized in that: The specific method of high temperature calcination in step (5) is: heating to 800° C. at a rate of 5° C. / min and then keeping the temperature for 2 hours.

8. A negative electrode material for a lithium-ion button battery, characterized in that: The method according to any one of claims 1 to 7 is used to prepare the present invention.

Citation Information

Patent Citations

  • Carbon-coated Na0.55 Mn2O4.1.5H2O nanocomposite and preparation method thereof

    CN105514375A

  • Silicon-carbon negative electrode material for lithium-ion battery and preparation method of silicon-carbon negative electrode material

    CN106129362A

  • Composite conductive adhesive suitable for silicon-based negative electrode of lithium ion battery

    CN111384398A

  • Crosslinked chitosan-derived silicon-carbon negative electrode material and preparation method thereof

    CN112993224A

  • Silicon-based negative electrode binder with topological three-dimensional structure, negative electrode plate, preparation method of negative electrode plate and battery

    CN117038991A